SEROPREVALENCE OF TOXOPLASMA GONDII IN FELIS CATUS IN HAVANA - Grandía G., Raiden (2013)
Toxoplasma gondii is a protozoan with a wide range of intermediate and definitive (felines) hosts and causal agent of toxoplasmosis, re-emergent zoonosis of worldwide distribution. The seroprevalence in humans in Cuba is high but the prevalence in the domestic cat in the capital city is unknown. The present study aimed to determine the seroprevalence of T. gondii in Felis catus in Havana, Cuba. A total of 300 serum samples from domestic cats were collected from 15 municipalities from October 2010 until April 2011. Samples were analysed by an ELISA Inhibition assay. Municipalities were grouped in a Central and in a Peripheral zone. The seroprevalence was 70%, without significant differences between zones and municipalities. The results allowed concluding that the seroprevalence of T. gondii in domestic cats in Havana was high, which constitutes a potential risk of infection for all hosts, including humans.